Regulatory Mechanisms of IL-33-ST2-Mediated Allergic Inflammation - Takatori, Hiroaki; Makita, Sohei; Ito, Takashi; Matsuki, Ayako; Nakajima, Hiroshi (Frontiers in Immunology, 2018)
Interleukin-33 (IL-33) plays multiple roles in tissue homeostasis, prevention of parasitic infection, and induction of allergic inflammation. Especially, IL-33-ST2 (IL-1RL1) axis has been regarded as the villain in allergic diseases such as asthma and atopic dermatitis and in autoimmune diseases such as rheumatoid arthritis. Indeed, a number of studies have indicated that IL-33 produced by endothelial cells and epithelial cells plays a critical role in the activation and expansion of group 2 innate lymphoid cells (ILC2s) which cause allergic inflammation by producing large amounts of IL-5 and IL-13. However, mechanisms that antagonize IL-33-ST2-mediated immune responses remain largely unknown. Recently, several groups including our group have demonstrated cellular and molecular mechanisms that could suppress excessive activation of ILC2s by the IL-33-ST2 axis. In this review, we summarize recent progress in the regulatory mechanisms of IL-33-ST2-mediated immune responses. Selective targeting of the IL-33-ST2 axis would be a promising strategy in the treatment of allergic and autoimmune diseases.